The O-glycosylated ectodomain of FXYD5 impairs adhesion by disrupting cell-cell trans-dimerization of Na,K-ATPase β1 subunits - Tokhtaeva, Elmira (2016)
FXYD5 (also known as dysadherin), a regulatory subunit of the Na,K-ATPase, impairs intercellular adhesion by a poorly understood mechanism. Here, we determined whether FXYD5 disrupts the trans-dimerization of Na,K-ATPase molecules located in neighboring cells. Mutagenesis of the Na,K-ATPase β1 subunit identified four conserved residues, including Y199, that are crucial for the intercellular Na,K-ATPase trans-dimerization and adhesion. Modulation of expression of FXYD5 or of the β1 subunit with intact or mutated β1?β1 binding sites demonstrated that the anti-adhesive effect of FXYD5 depends on the presence of Y199 in the β1 subunit. Immunodetection of the plasma membrane FXYD5 was prevented by the presence of O-glycans. Partial FXYD5 deglycosylation enabled antibody binding and showed that the protein level and the degree of O-glycosylation were greater in cancer than in normal cells. FXYD5-induced impairment of adhesion was abolished by both genetic and pharmacological inhibition of FXYD5 O-glycosylation. Therefore, the extracellular O-glycosylated domain of FXYD5 impairs adhesion by interfering with intercellular β1?β1 interactions, suggesting that the ratio between FXYD5 and α1?β1 heterodimer determines whether the Na,K-ATPase acts as a positive or negative regulator of intercellular adhesion.